2000
DOI: 10.1128/mcb.20.16.5986-5997.2000
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPα Inhibits Cell Growth via Direct Repression of E2F-DP-Mediated Transcription

Abstract: Using an inducible transcription system which allows the regulated expression of C/EBP isoforms in tissue culture cells, we have found that the ectopic expression of C/EBP␣, at a level comparable to that found in normal liver tissue, has a pronounced antimitogenic effect in mouse L cells and NIH 3T3 cells. The inhibition of cell division by C/EBP␣ in mouse cells cannot be reversed by simian virus 40 T antigen, by oncogenic ras, or by adenovirus E1a protein. When expressed in thymidine kinase-deficient L cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
133
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(141 citation statements)
references
References 53 publications
7
133
0
Order By: Relevance
“…C/EBP␣ may inhibit the G 1 /S transition via interaction with E2F or with cdk2. [57][58][59][60] Interaction with cdk2 occurs via the C/EBP␣ basic region, and this segment is retained in K␣ER. 60 Expression of p21 WAF1/CIP1 or p27 Kip1 in U937 cells induces monocytic markers.…”
Section: Discussionmentioning
confidence: 99%
“…C/EBP␣ may inhibit the G 1 /S transition via interaction with E2F or with cdk2. [57][58][59][60] Interaction with cdk2 occurs via the C/EBP␣ basic region, and this segment is retained in K␣ER. 60 Expression of p21 WAF1/CIP1 or p27 Kip1 in U937 cells induces monocytic markers.…”
Section: Discussionmentioning
confidence: 99%
“…It initiates growth arrest by stabilizing p21, and by disrupting E2F transcriptional complexes during the G1 phase of the cell cycle [7][8][9][10][11][12]. It was suggested that C/EBPα might be a tumor suppressor gene.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps C/ EBPa dimers are required for interaction with E2F or with another protein associated with the E2F complexes, or perhaps C/EBPa monomers interact with one of these proteins via its leucine zipper. In fact, E2F contains a leucine zipper, as noted (Slomiany et al, 2000). C/EBPe also slows 32D cl3 proliferation (Nakajima and Ihle, 2001).…”
Section: C/ebpsmentioning
confidence: 99%
“…Both C/EBPaWT-ER and KaER inhibit progression from G1 to S phase in 32D cl3 cells (Wang et al, 1999;Friedman and Wang, 2000). These proteins may inhibit the G1/S transition via interaction with E2F (Timchenko et al, 1999;Slomiany et al, 2000;Johansen et al, 2001). A KaER variant with a defective leucine zipper domain does not slow 32D cl3 proliferation (Wang and Friedman, 2002).…”
Section: C/ebpsmentioning
confidence: 99%